Distributed model predictive control of nonlinear systems subject to asynchronous and delayed measurements - Liu, Jinfeng; Muñoz de la Peña, David; Christofides, Panagiotis D. (Automatica (Oxford), 2010)
In this work, we design distributed Lyapunov-based model predictive controllers for nonlinear systems that coordinate their actions and take asynchronous measurements and delays explicitly into account. Sufficient conditions under which the proposed distributed control designs guarantee that the state of the closed-loop system is ultimately bounded in a region that contains the origin are provided. The theoretical results are demonstrated through a chemical process example.